Oxide ion conductivity in doped Ga based perovskite type oxide - Ishihara, Tatsumi (Elsevier B.V., 1996)
Oxide ion conductivity of Ga based perovskite type oxides, LnGaO, (Ln = Nd, La) and its related oxide, A,Ga,O, (A = Ba and St) was investigated. Oxide ion transference number is almost I.0 on Sr,Ga,O, or Ba,Ga,O,. However, electrical conductivity of these A,Ga,O, system oxides was lower than log (a/S cm-‘) = - 3 due to the low solubility of the aliovalent cations. On the other hand, doped perovskite type oxide of NdGaO, and LaGaO; exhibited a high electrical conductivity and the transference number of oxide ion was higher than 0.9 in the oxygen partial pressure range from PO2 = 1 to 1o-2’ atm. In particular, Ca and Mg doped NdGaO, exhibited a high oxide ion conductivity in similar with LaGaO,based oxide.